Failure Mode and Effects Analysis (FMEA) using Neutrosophic Best Worst Method (BWM) : A Case Study of Helicopter Assembly Line for Military Aviation Area - Dağıstanlı, Hakan Ayhan (Journal of Intelligent Decision Making and Information Science, 2025)
One of the most popular structured approaches in risk assessment is Failure Mode and Effects Analysis (FMEA) that helps in discovering potential failures existing within the design of a product or process. Determining the risk weights of failure types correctly is a critical part of the decision-making process of the analysis. In this study, the Best Worst Method (BWM) was integrated with the Neutrosophic Fuzzy Set and applied to the FMEA problem. The aim of the study is to determine the failure types encountered in the helicopter assembly line in the military aviation field and to offer solution suggestions. A case study was conducted for AH-64E Apache type helicopters for the effectiveness of the proposed method. The results show that gap and mismatch for structural elements, molds should not be used appropriately, unnecessary materials should be brought to the assembly line and attention should be paid to cabling problems.